2010
DOI: 10.1074/jbc.m110.139196
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Analysis of Partially Haploid Cells with Cre-mediated Chromosome Deletion in the Lymphoid System

Abstract: The fast accumulation of mutant mouse strains in recent years has provided an invaluable resource for phenotype-based genetic screens. However, study of lymphoid phenotypes can be obscured or impractical if homozygous mutations cause early embryonic defects. To aid phenotype screening of germ line mutations in the lymphoid system, we developed a method to induce loss of heterozygosity (LOH) in developing lymphocytes through chromosome deletion. Chromosome deletion was triggered by Cre/loxP-mediated inverse sis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Upon Cre expression, recombination between the duplicated sister chromatids yields either the same parental configuration or an inverted recombination to yield a pair of acentric and dicentric fragments ( Figure 1B). The acentric fragments are not maintained during repeated cell divisions and the dicentric fragments undergo breakage-fusion-bridge cycles in subsequent mitoses and are eventually lost (Zhu et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon Cre expression, recombination between the duplicated sister chromatids yields either the same parental configuration or an inverted recombination to yield a pair of acentric and dicentric fragments ( Figure 1B). The acentric fragments are not maintained during repeated cell divisions and the dicentric fragments undergo breakage-fusion-bridge cycles in subsequent mitoses and are eventually lost (Zhu et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…For brevity, we refer to cells with engineered chromosome loss events as ICLs (cells with Induced-Chromosome Losses) and their unrearranged parental counterparts as controls. Previous adaptation of this strategy, in the context of studying loss of heterozygosity (LOH), has shown that recombinationmediated marker loss also correlated strongly with chromosome loss in the lymphoid system in mice (Zhu et al, 2010), suggesting that marker loss is a faithful measure of the predicted chromosome loss event both in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Cre recombinase has been shown to be capable of driving recombination between sister chromatids via duplicated loxP sites [11], [12]. This recombination system provides an opportunity for Cre mediated activation of a genetic marker during cell cycle.…”
Section: Resultsmentioning
confidence: 99%
“…To test the efficiency of sister chromatid recombination, we isolated cells stably expressing GFP and transduced these cells again with a Cre-expressing retroviral vector. Efficiency of transduction was monitored with a hCD2 marker co-expressed with Cre on the retroviral vector [12]. Without cell cycle synchronization, the doubling time for NIH3T3 cells has been reported to be approximately 17 hours [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation